Association Between Cigarette Smoking And Cognitive Function In Stroke Patients Of Siloam Lippo Karawaci Hospital - Raspati, Raissa Putri; Gunawan, Pricilla Yani (Fakultas Kedokteran Universitas Pelita Harapan, 2021)
Stroke is cerebrovascular disease, causing deterioration of brain function as a result of cerebral blood flow disruption. Stroke is the third leading cause of death in the world and is considered an important cause of long-term disability and cognitive impairment. Risk factors of stroke are further divided into unmodifiable risk factors and modifiable risk factors, with one of the most common modifiable risk factors of stroke, is cigarette smoking. Besides being one of the risk factors that cause stroke, cigarette smoking is believed to have a role in cognitive impairment. This study aims to obtain information regarding the association between cigarette smoking and cognitive function in stroke patients of Siloam Lippo Karawaci Hospital. This research is an unpaired comparative analytical study with a cross-sectional design. Data sampling was taken by consecutive sampling on 56 stroke patients of Siloam Lippo Karawaci Hospital. Cognitive function was made based on the Montreal Cognitive Assessment version Indonesia (MoCA-INA). All data were analyzed by Chi-Square test using SPSS version 25 and the result is considered significant if the p-value < 0,05. From the result of this study. There is a significant association between cigarette smoking and cognitive function (p-value 0,004 and OR 5,343).